The Impact of Learning Management Systems (LMS) Based on Learning Analytics on the Academic Performance of Syiah Kuala University Students - Sofyan, H; Nasrudin, M F; Mailizar, M; Mahzum, E (Asian Journal of Science Education, 2024)
This study investigates the impact of Learning Management Systems (LMS) based on learning analytics on the academic performance of students in the Department of Physics Education at Universitas Syiah Kuala. Data were collected from 47 students, focusing on several indicators of LMS usage, including material access, task completion, and quiz participation. The analysis, as presented in Table 1, reveals significant positive correlations between LMS utilization and student GPA. Specifically, Pearson, Spearman, and Kendall correlation coefficients demonstrate strong associations (r 0.8, p 0.001) between the hours spent on the LMS and academic performance. Students frequently accessed learning materials more than completing assignments and quizzes, benefiting from the flexibility to study at their own pace. This adaptability is especially advantageous for students balancing academic and personal commitments, contributing to reduced stress levels and improved academic focus. The findings suggest that LMS utilization significantly enhances student GPA by enabling efficient time management and flexible learning schedules.